Robotic Surgery for the Treatment of Apical Pelvic Organ Prolapse at a Single Institution - Tayfun Toptaş; Aysel Uysal (Medical Network, 2017)
Objective: We sought to present implementation of robotic surgery for the treatment of apical pelvic organ prolapse at our clinic, with short-term outcomes. Study design: Clinical data of 11 consecutive patients with apical pelvic organ prolapse, who underwent robotic sacrocolpopexy or hysteropexy between July 2015 and August 2016, were collected prospectively. Primary endpoint of the study was anatomic cure and the secondary endpoint was symptomatic cure. Anatomic cure was defined as lack of anterior or posterior prolapse beyond the hymen and apical prolapse beyond the midvagina. Symptomatic cure was lack of vaginal bulge sensation. Results: Of the 11 patients, 9 underwent sacrocolpopexy and two underwent hysteropexy. Sacrocolpopexy was performed concomitantly with hysterectomy in 7 of the 9 patients. Mean operating time for all procedures was 254±65 minutes. No conversion to open surgery was required and no intraoperative complication was observed in any of the patients. The median hospital stay was 3 days. Four complications occurred postoperatively: 1 case of pulmonary thromboembolism, 2 cases of vaginal vault cellulitis and 1 case of mesh erosion. In total, 10 of 11 patients (90.9%) met the criteria for anatomic and symptomatic cure. Conclusion: Robotic pelvic support procedures can be readily adopted to routine clinical practice with high anatomic and symptomatic cure rates.